2012
DOI: 10.5812/aapm.4815
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Efficacy of Intra-Articular Application of Morphine and Tramadol on Postoperative Pain After Arthroscopic Knee Surgery

Abstract: Background:Intra-articular analgesia is a pain reliever that is frequently administered following arthroscopic knee surgery.Objectives:The purpose of this study was to compare the efficacy of intra-articular application of morphine and tramadol on postoperative pain after arthroscopic knee surgery.Patients and Methods:For this randomized double blinded clinical trial, 132 patients undergoing minor arthroscopic knee surgery were randomly assigned to receive either; 5 mg morphine or 50 mg tramadol intra-articula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Based on the results of our study, morphine suppository could relief pain after CABG. It seems that morphine can reduce postoperative pain effectively regardless of the route of administration ( 11 ). This study showed that using either of the suppository drugs, morphine sulfate or diclofenac sodium, in post-surgery CABG patients in ICU, can be effective in pain control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of our study, morphine suppository could relief pain after CABG. It seems that morphine can reduce postoperative pain effectively regardless of the route of administration ( 11 ). This study showed that using either of the suppository drugs, morphine sulfate or diclofenac sodium, in post-surgery CABG patients in ICU, can be effective in pain control.…”
Section: Discussionmentioning
confidence: 99%
“…Diclofenac can be prescribed as 50-100 mg suppository with the maximum dosage of 150 mg per day in two or three divided doses in adults. Quick absorption through rectum has been shown ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stein et al showed that low doses of IA morphine, injected on the completion of arthroscopic knee surgery, can produce postoperative analgesia via activation of local opioid receptors in the knee joint ( 24 ). This peripheral effect of narcotic-like analgesics could explain why the IA administration of morphine and tramadol could provide a satisfactory pain relief state as well as fewer systemic adverse effects ( 25 ). Morphine, as an opioid, and bupivacaine, as a local anesthetic, alone or compound form, are frequently injected into the IA space of the knee joint after arthroscopic surgery ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…We had lower VAS scores, decreased 24-hour total analgesic consumption in local anesthetic administration of tenoxicam-tramadol in comparison with saline group, which was similar to abovementioned studies. Jazayeri et al compared the efficacy of morphine and tramadol on postoperative pain after arthroscopic knee surgery ( 25 ). They had comparable VAS scores between two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In one study it was demonstrated that administration of Dextromethorphan prior to abdominal surgery decreased the need for postoperative opioids significantly compared to the placebo group ( 9 ). Also, Dextromethorphan has been successfully used to relieve postoperative pain following mastectomy, hysterectomy, and diagnostic laparoscopy ( 8 , 10 ). Considering the relevant literature, it seems that Dextromethorphan is effective in decreasing postoperative pain in patients and reduces administration of opioids.…”
Section: Introductionmentioning
confidence: 99%